1986
DOI: 10.1159/000265458
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Controlled Freezing of Human Donor Corneae

Abstract: A simple method for freezing cultured human donor material with dimethyl sulfoxide (DMSO) was developed empirically in a commercially available microcomputer-controlled apparatus allowing reproducible freezing curves to be made. The optimum cooling rate was found to be 1.0 °C/min down to –40 °C and then 5.0 °C/min to –80 °C. Total cell loss rates were 36.9 ± (SD) 19.8% of postmortem endothelial cell counts. An improved method for evaluating endothelial viability was applied, which enabled us to observe definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The experimental design employed here has been widely used in organ transplant research for establishing the postmortem viability of different body organs, such as kidneys, heart, bone, and cornea (2,12,22,23). These studies were taken into consideration when choosing the different time intervals to be evaluated (6, 12, and 24 hours).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental design employed here has been widely used in organ transplant research for establishing the postmortem viability of different body organs, such as kidneys, heart, bone, and cornea (2,12,22,23). These studies were taken into consideration when choosing the different time intervals to be evaluated (6, 12, and 24 hours).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study showed that 89.9% of pulp cells remained viable 6 hours after death; cell viability had decreased to 67.8% 12-hour postmortem. From a biological point of view, pulp could be considered to be a viable tissue at this point, taking into consideration that tissue is still biologically viable when at least 50% of its cells are vital (7,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation